Mutagenicity, clastogenicity and antimutagenicity of medicinal plant tablets produced by the NSTA Pilot Plant II. sambong tablets - Lim-Sylianco , C. Y.; Blanco, F.R.B; Lim, C.M (1987)
Sambong tablets prepared by NSTA Pilot plant did not show direct DNA damaging capacity. These tablets were not mutagenic before and after activation and they did not possess chromosome-breaking fluid. However, these tablets reduced the formation of micronucleated polychromatic erythrocytes induced by dimethylnitrosamine, tetracycline and mitomycin C suggesting that "sambong" tablets possess antimutagenicity activity.